"Internet Gaming Disorder" in China: Biomedical Sickness or Sociological Badness?. (May 2016) - Bax, Trent
"Internet addiction" in China and elsewhere is considered a serious social problem. In China, some psychiatrists have claimed 10% of all Internet users—60 million—are potentially "addicted" to the Internet. Following on the heels of the publication of the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders ( DSM-5 ), this qualitative-based research article critically investigates the new concept Internet gaming disorder, a category recently included in the DSM-5 as a condition "warranting more clinical research and experience before it might be considered for inclusion in the main book as a formal disorder." This article takes up this challenge and responds in the following way: When we investigate the social existence of online gamers labeled Internet addicts in China, and then subject their social existence to the DSM 's own definition of a mental disorder, we discover not a clearly understood mental disorder called Internet gaming disorder but more so an issue of social deviance.